BALANCE OF BIRTH AND MIND AS AN EFFORT TO MAINTAIN FAMILY HARMONY (HADITH STUDY NARRATED TIRMIDHI) - M. Ali Mubarok; Desi Anggraeni, Muhammad Aji Nugroho (CV. Adiba Aisha Amira, 2024)
A wife has been created by God for husbands to have a peaceful life with their families. Peace obtained by a husband to guide his wife to be achieved if the husband and wife cooperate in harmony, harmony and balance. This research will examine the hadith about the relationship between husband and wife. The author will examine a hadith, namely the hadith narrated by Tirmidhi No. 3.896 which states that a good man is one who does good to his family. The purpose of this study is to examine the quantity and quality of the hadith narrated by Tirmidhi about the relationship between husband and wife and to find out the picture in the community about the balance of birth and mental maintenance as an effort to maintain family harmony in Kembangsari Village. This research method is a mix method, namely library research and field research. From the research, it was found that the hadith narrated by Tirmidhi No. 3,896 about the relationship between husband and wife is mutawatir and saheeh. The fulfillment of birth and mental support in Kembangsari Village to maintain family harmony is very important, based on this hadith, a husband must also do good to his wife, especially in fulfilling birth and mental support. The second most important part is to foster and maintain communication between husband and wife in order to create a strong relationship with each other so that when a problem arises in the household, the husband and wife can overcome and solve it wisely, wisely and lovingly.